On-Line Access - A Beginner’s First Lesson - Sathyanarayana, N. V. (Journal of Information and Knowledge, 1987)
The development of on-line access to information system is presented in a step by step Fashion. The telecommunication alternatives, productive interaction using search aids, the result of information retrieval, particularly bibliographic reference retrieval are discussed.